Coastal Studies in James Bay, Ontario - Martini, I.; Morrison, R.; Glooschenko, W.; Protz, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1980)
Abstract Interdisciplinary studies have endeavoured to understand the geomorphology, sediments, soils, vegetation, and wildlife of the Ontario coast of James Bay, which is unique for its fast emergence (70 to 100 cm/century) related to post-glacial isosta-tic rebound. From a geomorphological-sedimentological point of view, the coast has many similarities to other mesotidal settings, although typical features due to ice-rafting and scouring of arctic and subarctic areas are recorded in thin (3 m) sedimentary sequences. Gleysolic soils form in its low-lying wetlands, and Regosolic soils evolve into Podzolic soils on sandy and gravelly beach ridges as they emerge and become forested. The vegetation of the marshes is typical of subarctic areas. The most common colonizing plants of intertidal zones are Puccinellia phryganodes in salt marshes, and Hippurus vulgaris in brackish marshes. Associated with large rivers, inverted marshes occur with brackish zones near the shoreline, and saltier zones inland due to evaporation of waters brought in by storm surges. The fauna of this coast ranges from numerous mosquitoes and other insects, to invertebrates, to migratory birds. The shore has irreplaceable international importance because it contains the breeding and feeding grounds of the migratory avifauna of central and eastern America. Tens of thousands of shorebirds and waterfowl feed on specific parts of the ecosystem depending on their food requirements and their anatomical limitations imposed by depth of burrowing of infauna, depth of water in marsh pools, and height of vegetation indifferent marshes at different times of the year. Whereas studies of this virgin, rapidly changing environment can help in understanding and perhaps managing the wildlife resource, and in predicting the response of the coastal zone to future human activities, such as regulation and diversion of rivers, all these processes leave their imprints in the sedimentary and soil sequences. In sedimentological terms the study of this coast will lead to a definition of a recognizable model of a cold, brackish, shallow, regressive, inland sea similar to those that have occupied this area during Pleistocene times, or other more ancient, emergent, glacial, arctic basins.